2015
DOI: 10.1063/1.4929424
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent-voltage relation of resonant tunneling diode photodetectors

Abstract: Photocurrent spectroscopy of intersubband transitions in GaInAsN/(Al)GaAs asymmetric quantum well infrared photodetectors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…A three dimensional color-coded sketch of the RTD photodetector is shown in Figure 1 ( given in Refs. [13,15]. The schematic conduction (CB) and valence band (VB) profile under an applied bias voltage is shown in Figure 1 occurs and hence the photocurrent vanishes almost completely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A three dimensional color-coded sketch of the RTD photodetector is shown in Figure 1 ( given in Refs. [13,15]. The schematic conduction (CB) and valence band (VB) profile under an applied bias voltage is shown in Figure 1 occurs and hence the photocurrent vanishes almost completely.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to APDs, the RTD device performance is tuned by the applied bias voltage. In a recent publication, 13 we found that the RTD photocurrent-voltage relation is a nonlinear function, which can be described by three voltagedependent parameters: the RTD current-voltage characteristics in the dark , the RTD quantum efficiency , and the mean lifetime of photogenerated holes accumulated in vicinity to the resonant tunneling structure. Furthermore, the RTD photocurrent-voltage relation is not only a nonlinear function of the applied bias voltage, but also a nonlinear function of the incident illumination power .…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, RTD-PDs enable high multiplication factors due to the possibility of controlling the tunneling current via Coulomb interaction of photo-generated minority charge carriers. 25 In recent publications, we studied the electrical characteristics of RTDs based on GaSb/AlAsSb double barrier structures and demonstrated room temperature resonant tunneling by incorporation of ternary GaAsSb or GaInSb prewells. 26,27 In this study, we present resonant tunneling diode photodetectors with a GaAsSb/AlAsSb double barrier regions.…”
mentioning
confidence: 99%
“…[12][13][14] This mechanism provides very high amplification factors exceeding several hundred thousand at considerably low operation voltages. 10,11,15,16 The GaSb/InAs/AlSb material system has brought forth resonant tunneling structures (RTS) with unique and enhanced characteristics. prewell emitters leads to room temperature resonant tunneling with peak-to-valley current ratios of 1.45 and The HR-XRD spectrum of RTD 1 shows a single peak at Δ 0°, which indicates a good and high quality latticematched crystal growth of the RTD and the AlGaAsSb contact region.…”
mentioning
confidence: 99%